Different roles of municipalities in a urban agglomeration: a regional agent-based economic model - Moreno Baruffini; Valentina Mini; Luzius Stricker (European Regional Science Association (ERSA), 2015)
Historically Switzerland is characterized by numerous small towns. During the twentieth century, the image of Swiss cities has changed: the expansion of the city has reached the limits of administrative urban borders, penetrating in peripheral locations. The main reasons concern not only the territorial environment, but also the possibility to support public services and public investments. Currently, urban agglomerations include dozens of municipalities and this is seen as a virtuous strategy to provide basic public services and utilities in peripheral areas. Swiss federalism has fostered the development of a large number of small and medium sized cities. This creates the conditions for polycentric and decentralized settlements. At this stage of the territorial and institutional transformation, the understanding of different municipalities? roles is essential: the ?work? and ?live? functions are spread irregularly throughout the territory. Some core cities are traditionally business locations but the progressive urbanization has enhanced the attractiveness of the belt municipalities, for both residential and business purposes. We try to identify the different functions and relations between 47 agglomerated municipalities in southern Switzerland (Ticino), using a territorial agent based model. The analysis focus on four analytical dimensions: economic competitiveness, attractiveness, openness and social equality. Our research adopts a bottom up approach to urban systems, considering the agglomeration mechanism and effects of different regional and urban policies. Urban residential dynamics are the result of simultaneous household?s choices; thus, no program can be planned, without the ability to understand and predict the individual decisions in the short and long term. Recently, agent based models (ABMs) have been proposed in order to support urban policy makers. Simulating the individual actions of diverse agents on a real city and measuring the resulting system behaviour and outcomes over time, they provide a good test bed for evaluating the impact of different policies Our analysis starts from the micro level at the smallest territorial unit (municipalities). The database is created merging the Swiss official secondary data for one reference year (2011) with Eurostat and OECD Regpat. The model, linking territorial characteristics and agents, simulates the single location choices and formation of urban development patterns, which are influenced by residential and industrial agglomeration forces and policy interventions. The results highlight that the understanding of municipalities? functions on the territory appears to be essential for designing a solid institutional agglomeration (or city). From a methodological point of view, we contribute to improve the application of territorial ABMs. Finally, our results provide a robust base to evaluate in a dynamic way various political interventions, in order to ensure a sustainable development of the agglomeration and the surrounding territories.
Keywords: C63; R12; R14; 330; urban agglomeration; urban policy evaluation; Agent Based Models